Patents at the Crossroads: Legal Pathways for Advancing Technology Transfer in Indonesia - Sujatmiko, Agung; Romadhona, Mochamad Kevin; Saraswati, Yuniar Rizky (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2025)
Indonesia needs technology for industrial infrastructure, but it is still controlled by developed countries. Patent licensing agreements can help facilitate this process. However, Indonesia's patent registrations are slow due to a lack of regulations and internal factors.This study aims to analyze the role of patent licensing in transferring technology from developed to developing countries. Patent license agreements play a crucial role as a mechanism for technological development. Therefore, it is essential to find solutions to ensure an effective transfer of technology.This research employs a statutory and conceptual approach. The analysis follows a deductive method by examining general laws and regulations before drawing conclusions.The results show that several regulations related to technology transfer serve as the main reference for understanding why technology transfer is difficult to achieve and identifying its underlying causes. Once these causes are identified, appropriate solutions can be proposed. The lack of regulations in Indonesia’s legal framework for technology transfer hinders its full potential. In conclusion, Indonesia's technology transfer laws have not been effective due to the absence of clear implementation guidelines and strict penalties. Therefore, a specific law regulating technology transfer is needed, emphasizing its importance and benefits while ensuring a strong commitment from all relevant parties.